Nationalist Approach in Appropriating Traditional and Modern Identity in Wole Soyinka’s The Lion and the Jewel - Nazneen Zahra; Dr. Shamshad Rasool; Dr. Behzad Anwar (University of Chitral Journal of Linguistics and Literature, 2022)
Wole Soyinka, an African dramatist, has represented Nigerian culture and traditions in his works. He has highlighted the post-colonial context and the resistance by the natives to European cultural hegemony. This research paper aims at exploring the nationalist approach in explaining the current state of values and the attitude of people in Nigeria through a nationalistic idea that ascribes gender roles in its attempt to retain true self-identity. The nationalistic approach propounded by Fanon (1967) has been employed as the framework on Soyinka’s play The Lion and the Jewel. The study finds out that Soyinka has highlighted gender roles and the customs related to marriage, bride price and the relation between husband and wife. He emphasizes the responsibility of women in terms of defining their roles and retaining their values by accepting the prescribed status assigned to them in a patriarchal setup.